2015
DOI: 10.1158/1078-0432.ccr-14-3023
|View full text |Cite
|
Sign up to set email alerts
|

APO866 Increases Antitumor Activity of Cyclosporin-A by Inducing Mitochondrial and Endoplasmic Reticulum Stress in Leukemia Cells

Abstract: Purpose: The nicotinamide phosphoribosyltransferase (NAMPT) inhibitor, APO866, has been previously shown to have antileukemic activity in preclinical models, but its cytotoxicity in primary leukemia cells is frequently limited. The success of current antileukemic treatments is reduced by the occurrence of multidrug resistance, which, in turn, is mediated by membrane transport proteins, such as P-glycoprotein-1 (Pgp). Here, we evaluated the antileukemic effects of APO866 in combination with Pgp inhibitors and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
(62 reference statements)
0
28
0
Order By: Relevance
“…As tumor cells always have very high intracellular NAD turnover, which is supportive for the increased metabolic demands in rapid proliferation by generating more ATP/energy [42], NAMPT overexpression is rather common in many types of tumor, including leukemia [43, 44] and solid tumor [812]. Indeed, Zoppoli et al reported that NAMPT inhibitor FK866 resulted in autophagic cell death in primary B-cell chronic lymphocytic leukemia cells via inducing NAD + depletion, mitochondrial transmembrane potential (ΔΨ m ) dissipation, and ATP shortage [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As tumor cells always have very high intracellular NAD turnover, which is supportive for the increased metabolic demands in rapid proliferation by generating more ATP/energy [42], NAMPT overexpression is rather common in many types of tumor, including leukemia [43, 44] and solid tumor [812]. Indeed, Zoppoli et al reported that NAMPT inhibitor FK866 resulted in autophagic cell death in primary B-cell chronic lymphocytic leukemia cells via inducing NAD + depletion, mitochondrial transmembrane potential (ΔΨ m ) dissipation, and ATP shortage [44].…”
Section: Discussionmentioning
confidence: 99%
“…When FK866 was used with tumor necrosis factor-related apoptosis-inducing ligand in leukemia cells, there was a synergistical action in their toxicity towards leukemia cells [44]. Cagnetta et al confirmed that combined use of FK866 and p-glycoprotein-1 inhibitors showed a strong synergistic cooperative suppression of acute myelogenous leukemia (AML) and B-cell chronic lymphocytic leukemia (B-CLL) sample [43]. In solid tumor, including tumors derived from kidney [45], pancreas [46], lung [47], and breast [48], NAMPT inhibitors have displayed portent anticancer effect.…”
Section: Discussionmentioning
confidence: 99%
“…Nampt-targeting emerges as effective approach not only when coupled to standard chemotherapy, including DNA damaging agents [16] but also in combination with more modern, molecularly-targeted agents (such as ibrutinib, cyclosporin A and bortezomib) [8,9,13].…”
Section: Nampt Inhibitorsmentioning
confidence: 99%
“…As a result, Nampt inhibitors as monotherapy have demonstrated potent antitumor activity in preclinical cancer models [3][4][5][6][7]. In such a scenario, investigators have also tested NAD + -depleting agents in combination with antineoplastic agents, chemotherapy, or radiotherapy in a wide range of hematological malignancies, including AML, MM, and lymphomas, observing an increased activity and overall tolerability of these agents [8][9][10][11][12]. Thus, several clinical trials are currently exploring such metabolic vulnerability in patients undergoing chemotherapy (NCT02702492, NCT00435084, and NCT00431912).…”
mentioning
confidence: 99%
“…Thus, its aberrant activation has been reported in a number of solid and hematologic malignancies, including leukemia and multiple myeloma. (7, 8) Based on these observations, tumor cells are more susceptible to Nampt inhibition than normal cells. (8-12) Indeed, targeting Nampt with the specific inhibitor FK866 represents a novel therapeutic strategy for human cancer.…”
Section: Introductionmentioning
confidence: 99%